American tegumentary leishmaniasis in the population of the city of Rio Branco, Acre, Brazil: a 2007–2015 time series analysis - da Costa Moreira, Analdemyra; de Souza, Orivaldo Florencio; de Oliveira Cardoso, Cristiane (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
American tegumentary leishmaniasis (ATL) is a public health problem in the State of Acre. This study analyses the incidence of all forms of ATL time series in the human population from 2007 to 2015. This time series ecological study investigated the incidence of all forms of ATL in the city of Rio Branco, Acre, Brazil. Data on the number of cases of all forms of ATL diagnosed from 2007 to 2015 were collected from the secondary Health Surveillance Board database, Rio Branco City Health Department. Prais–Winsten regression was used to analyze the trends in ATL incidence. Subsequently, the annual percent change (APC) was estimated. The incidence of disease remained stationary during the studied period, except in the age group from 15 to 19 years old with an increase in the annual variation percentage (APC: 6,48%; IC95%: 1,67; 11,53) and a decline between 20 and 34 years old (APC: -15,41%; IC95%: -18,57; -12,13) and 35 and 49 years old (APC: -8,52%; IC95%: -14,63; -1,97). There was a higher frequency of cases between 2007 and 2015 in the cutaneous form, entry of new cases, evolution to cure, and diagnosis by clinical-laboratory procedures. In conclusion, there was a high disease incidence during the studied period. Additionally, an increase in the ATL incidence in the younger age group and a decrease in the ATL incidence in the middle age groups were observed. KEY WORDS: Cutaneous leishmaniasis; time series study; incidence.